ANALYSIS AND EVALUATION OF EDUCATIONAL MATERIALS IN TEACHING FOREIGN LANGUAGES - Xakimova Munira Xabibullayevna; Turmuhammadova Sevinch Akmal qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract Article presents a comprehensive analysis and evaluation of educational materials used in the teaching of foreign languages. It explores the criteria for selecting effective materials, including authenticity, cultural relevance, and alignment with learners’ needs and goals. The study emphasizes the importance of integrating diverse resources, such as textbooks, digital tools, and multimedia content, to enhance language acquisition and engagement. Additionally, it examines the role of teachers in adapting and supplementing materials to cater to different learning styles and contexts. By assessing various types of educational resources, this research aims to provide insights into best practices for language instruction and the development of effective curricula.